2013
DOI: 10.3389/fgene.2012.00317
|View full text |Cite
|
Sign up to set email alerts
|

Genetical Genomics Reveals Large Scale Genotype-By-Environment Interactions in Arabidopsis thaliana

Abstract: One of the major goals of quantitative genetics is to unravel the complex interactions between molecular genetic factors and the environment. The effects of these genotype-by-environment interactions also affect and cause variation in gene expression. The regulatory loci responsible for this variation can be found by genetical genomics that involves the mapping of quantitative trait loci (QTLs) for gene expression traits also called expression-QTL (eQTLs). Most genetical genomics experiments published so far, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 90 publications
6
58
1
Order By: Relevance
“…This observation is strengthened by the variance component analysis that indicated a clear role for trans-located SNPs for explaining the expression variation. Previous studies on RIL populations identified mainly cis variation to be associated with gene expression in general Keurentjes et al, 2007), whereas the environment-dependent expression showed enrichment in trans regulators (Cubillos et al, 2014;Lowry et al, 2013;Snoek et al, 2013). This general trend corresponds to our results; however, the absence of cis regulators for environmentdependent expression is striking, especially because cis loci typically have stronger effects on gene expression compared with trans (Fusi et al, 2012).…”
Section: Diversity Of Potential Regulators Of Gene Expressioncontrasting
confidence: 54%
“…This observation is strengthened by the variance component analysis that indicated a clear role for trans-located SNPs for explaining the expression variation. Previous studies on RIL populations identified mainly cis variation to be associated with gene expression in general Keurentjes et al, 2007), whereas the environment-dependent expression showed enrichment in trans regulators (Cubillos et al, 2014;Lowry et al, 2013;Snoek et al, 2013). This general trend corresponds to our results; however, the absence of cis regulators for environmentdependent expression is striking, especially because cis loci typically have stronger effects on gene expression compared with trans (Fusi et al, 2012).…”
Section: Diversity Of Potential Regulators Of Gene Expressioncontrasting
confidence: 54%
“…In total, 47 fractions were collected and pooled into 10 fractions based on the intensity measured by a UV-light detector at 214 nm. The reproducibility of the separation was controlled by running twice a self-mixed standard peptide mixture (adrenocorticotropin(1-16), angiotensinogen (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), bradykinin(2-9), leu-enkephalin, substance P, and vasopressin). Pooled fractions were vacuum-centrifuged until complete dryness and resuspended in 50 l of 5% ACN, 0.1% TFA.…”
Section: Methodsmentioning
confidence: 99%
“…The broad-sense heritable variation in gene expression has been estimated to be up to 70% in the nematode Caenorhabditis elegans (3,4) and up to 80% in yeast (5). This high heritability and the ability to construct genetically segregating populations facilitate mapping of gene expression regulation and subsequent detection of expression quantitative trait loci (eQTL) 1 (5)(6)(7)(8)(9)(10)(11). eQTLs are genomic regions containing a polymorphism associated with variation in transcript abundance between genotypes (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, gene expression can vary among individuals of a species due to natural genetic variation (G), and some genes may further exhibit genetic variation in their expression in response to the environment (expression GxE interactions). One promising avenue for studying natural variation in gene expression is through expression quantitative trait locus (eQTL) mapping (Li et al, 2006;Smith and Kruglyak, 2008;Keurentjes et al, 2007;Breitling et al, 2008;Fu et al, 2009, Cubillos et al, 2012a, 2012bSnoek et al, 2012). Here, mRNA transcript abundance for each gene in the genome is treated as a trait for genetic mapping.…”
Section: Introductionmentioning
confidence: 99%